Preparation and application of a porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent

By preparing ethylenediamine modified column aromatic bonded porous silicon material, porous column aromatic solid amine carbon dioxide adsorbent, the problems of poor selectivity and low capacity of existing porous materials in carbon dioxide capture are solved, and efficient and stable carbon dioxide adsorption are achieved Effect.

CN116983959BActive Publication Date: 2025-02-11LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311030582.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-11
Estimated Expiration
2043-08-16

AI Technical Summary

Technical Problem

Existing porous materials have problems such as poor selectivity, low capacity and poor adsorption capacity in the capture or adsorption of carbon dioxide, which is difficult to meet the needs of efficiently trapping carbon dioxide.

Method used

By preparing ethylenediamine modified column aromatic bonded porous silicon material, a porous column aromatic solid amine carbon dioxide adsorbent is formed, leveraging its potential for high capacity and selective adsorption of carbon dioxide.

Benefits of technology

The adsorbent exhibits a high carbon dioxide saturated adsorption amount under specific conditions, reaching 7.8 mmol/g, and maintains stable adsorption performance in 10 consecutive cycle adsorption experiments, proving its high efficiency and stability in the field of carbon dioxide capture. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention provides a preparation and application of a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The present invention uses columnar aromatic hydrocarbon bonded amino porous silicon to further react with ethylenediamine for halogenation, and then bonded with collodion solution, calcined and granulated to prepare a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The adsorbent material has a high adsorption capacity in the efficient adsorption and removal of carbon dioxide in the field of carbon emission reduction. The saturated adsorption amount of the penetration curve reaches 7.8 mmol / g under the conditions of 20 ml / min and 40 degrees Celsius, and the saturated adsorption amount of carbon dioxide can still be maintained at a high adsorption capacity of 6.2 mmol / g after 10 consecutive cycle adsorption experiments. The porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent has a simple preparation process, high carbon dioxide gas adsorption capacity and strong stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon emission reduction under the background of "double carbon" in environmental engineering, and specifically to the preparation of ethylenediamine modified column [5] aromatic hydrocarbon bonded silica gel porous solid amine adsorbent and the evaluation of carbon dioxide adsorption performance. Background Art

[0002] The emission of greenhouse gases such as carbon dioxide, methane, and nitrogen oxides is the main problem causing global climate change, the "greenhouse effect". And with the further burning of fossil fuels and the intensification of industrial activities, this problem will become more and more serious. So far, carbon dioxide capture and storage technology is considered to be one of the most promising ways to reduce the concentration of carbon dioxide in the atmosphere. There are many carbon dioxide capture technologies, such as chemical / physical absorption, chemical adsorption, and membrane separation. Among them, the efficient capture or adsorption of carbon dioxide is of great research value because of its large adsorption capacity, simple operation process, and easy regeneration.

[0003] In recent years, various types of solid amine adsorbents with structures such as zeolite, resin, porous carbon, metal organic framework, etc. have been widely used for the capture or adsorption of carbon dioxide, but most of them rely on the physical adsorption effect of the pore structure. There are problems such as poor selectivity, low capacity, and poor adsorption capacity. In order to improve the adsorption capacity and selectivity of these porous materials for carbon dioxide, and maintain the effect of increasing the amount of carbon dioxide adsorption at the same time, various amines are loaded onto porous materials and supramolecular materials through multi-site chemical grafting to prepare porous solid amine adsorbents. This adsorbent may have great potential for high capacity or selective adsorption of carbon dioxide. However, there are few reports on the capture or adsorption of carbon dioxide by high-capacity and high-selectivity supramolecular solid amine adsorbents, which are expected to be used for efficient capture of carbon dioxide in actual industrial applications. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent and to study the carbon dioxide adsorption performance of the adsorbent.

[0005] 1. Preparation and characterization of porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent

[0006] 1. Preparation of porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent

[0007] (1) Synthesis of brominated pillar aromatics: Dissolve 1,1-dibromophenylene diethyl ether in 1,2-dichloroethane solution, add paraformaldehyde as polymerization reagent, boron trifluoride ether as catalyst, and react under nitrogen protection and stirring at room temperature for 1.1 to 1.5 hours. After the reaction, filter, wash, dry, and purify by column chromatography to obtain brominated pillar aromatics. The mass ratio of 1,1-dibromophenylene diethyl ether to paraformaldehyde is 2.2:1 to 3.0:1; the mass ratio of 1,1-dibromophenylene diethyl ether to boron trifluoride ether is 1.4:1 to 1.7:1.

[0008] The synthetic route is as follows:

[0009] .

[0010] (2) Preparation of porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent: aminopropyl silica gel is dispersed in anhydrous toluene, and brominated columnar aromatic hydrocarbon, ethylenediamine, and catalyst tetrabutylammonium bromide are added. The mixture is refluxed at 85-90°C for 45-48 hours. After the reaction is completed, a light yellow solid powder is obtained by filtration. The powder is washed and vacuum dried to obtain an ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material. The ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material is added to an ethanol solution containing collodion, stirred evenly, and the solvent is removed under reduced pressure. The obtained material is dried, ground, and sieved to obtain a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent.

[0011] Among them, the mass ratio of aminopropyl silica gel to brominated pillar aromatics is 2.1:1~2.8:1; the mass ratio of brominated pillar aromatics to ethylenediamine is 0.7:1~0.9:1; the mass ratio of brominated pillar aromatics to catalyst tetrabutylammonium bromide is 11:1~16:1.

[0012] The synthetic route is as follows:

[0013] .

[0014] 2. Scanning electron microscope

[0015] The obtained porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent was characterized by scanning electron microscopy. Figure 1 As shown, from the scanning electron microscope image magnified 2000 times, it can be seen that the adsorbent presents a uniform porous silicon stacking pore structure, and these pore structures will be more conducive to the efficient capture or adsorption of carbon dioxide.

[0016] 3. Infrared spectrum

[0017] The infrared spectrum of the adsorbent is shown in Figure 2As shown, the characteristic peaks at 1458 and 3423 wavenumbers are the vibration peaks of −NH2 and −N−H, respectively, and the characteristic peaks at 2938 and 2858 wavenumbers are the symmetric stretching and asymmetric stretching vibration peaks corresponding to the -CH2 bond. The characteristic peak at 1648 wavenumber is the stretching vibration peak of NH in primary amine (-NH2), and the characteristic peak at 1482 wavenumber is the deformation vibration absorption peak of the CH bond. The characteristic peaks at 1093, 810 and 467 wavenumbers are the characteristic vibration peaks of the Si-O-Si bond in porous silica. In addition, the enhanced transmittance of the characteristic peak at 3442 wavenumber confirms the successful modification of ethylenediamine. The infrared results show the successful preparation of porous columnar aromatic solid amine carbon dioxide adsorbent.

[0018] 4. Elemental analysis

[0019] The results of elemental analysis showed that the nitrogen, carbon and hydrogen contents of aminopropyl silica gel were 1.40%, 4.34% and 0.91% respectively, while the nitrogen, carbon and hydrogen contents of porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent were 3.10%, 14.21% and 1.52% respectively. The results of elemental analysis proved the successful preparation of porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent. The specific experimental data are shown in Table 1.

[0020]

[0021] 2. Carbon dioxide capture or adsorption performance of porous column aromatic solid amine adsorbent

[0022] 1. Flow rate investigation

[0023] The CO2 adsorption process was carried out in a fixed bed reactor. Flow rate is an important factor affecting the adsorption capacity of the adsorbent because the gas flow rate is closely related to mass transfer. The experimental results show that at 30 degrees Celsius, the CO2 adsorbent with 0.2 g of porous column aromatic solid amine increases from 5 to 30 ml / min ( Figure 3 ) penetration curve, it can be observed that with the increase of carbon dioxide gas flow rate, the saturated adsorption capacity of the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent shows a trend of first increasing and then decreasing. When the gas flow rate is ml / min, the saturated adsorption capacity of carbon dioxide is the largest, reaching 6.8 mmol / g. However, when the gas flow rate is further increased, the amino groups on the surface of the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent have fully reacted with carbon dioxide to form a stable structure, and the mass transfer resistance increases, making it difficult for the amino groups in the pores or mesopores to further fully react, and the contact time is shortened, thereby reducing the saturated adsorption capacity of carbon dioxide. Therefore, 20 ml / min is the optimal flow rate for the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent.

[0024] 2. Inspection of adsorbent quality

[0025] Under the conditions of flow rate of 20 ml / min and temperature of 30 degrees Celsius, the effect of the amount of porous column aromatic solid amine carbon dioxide adsorbent on the carbon dioxide adsorption capacity was investigated. It was found that as the amount of porous column aromatic solid amine carbon dioxide adsorbent increased from 0.2 g to 0.8 g, the carbon dioxide saturated adsorption capacity decreased from 6.8 mmol / g to 2.4 mmol / g, and the breakthrough time became shorter ( Figure 4 ). According to the adsorption mechanism of acidic gas carbon dioxide, its adsorption capacity mainly depends on the amine content of the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent. However, if too much porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent is filled in a limited reaction tube, as the column height further increases, the diffusion resistance of carbon dioxide through the adsorbent pores increases, and the contact time with the internal adsorbent active amine sites decreases, and the adsorption capacity decreases. Therefore, 0.2 grams is the optimal adsorbent mass condition.

[0026] 3. Temperature inspection

[0027] Under the conditions of a flow rate of 20 ml / min and an adsorbent mass of 0.2 g, the effect of temperature change on the adsorption of carbon dioxide by the porous column aromatic solid amine carbon dioxide adsorbent was investigated. It was found that as the temperature increased, the adsorption of carbon dioxide by the porous column aromatic solid amine carbon dioxide adsorbent increased accordingly. At 40 degrees Celsius, it reached 7.8 mmol / g. As the temperature further increased, the saturated adsorption of carbon dioxide decreased to 3.7 mmol / g, and the breakthrough time became shorter ( Figure 5 ). Perhaps it is because the temperature increases, the molecular motion intensifies, and the contact time between the carbon dioxide molecules and the amino active groups on the porous column aromatic solid amine carbon dioxide adsorbent becomes shorter, resulting in a decrease in the saturated adsorption capacity. Therefore, 40 degrees Celsius is selected as the optimal condition.

[0028] 4. Cycle repeatability test

[0029] Good reproducibility or recyclability is of great significance to the practical application of adsorbents. Therefore, under the conditions of a flow rate of 20 ml / min, an adsorbent mass of 0.2 g, and a temperature of 40 degrees Celsius, the porous column aromatic solid amine carbon dioxide adsorbent was tested for 10 consecutive cycles of adsorption performance. The experiment found that as the number of tests increased, the saturated adsorption capacity of carbon dioxide could still be maintained at 6.2 mmol / g ( Figure 6 ). Therefore, the ethylenediamine-modified pillar aromatic hydrocarbon-bonded porous silicon has an obviously stable surface amino group, and the amino group loss rate is low during the regeneration process, and the stability is good.

[0030] In summary, the present invention uses columnar aromatic hydrocarbon bonded amino-modified porous silicon to further react with ethylenediamine for halogenation, and simply prepares a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The adsorbent material has a high adsorption capacity in the field of carbon emission reduction for efficient adsorption and removal of carbon dioxide. The penetration curve saturation adsorption capacity of 0.2g of porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent reaches 7.8 mmol / g under the conditions of 20 ml / min and 40 degrees Celsius, and the saturated adsorption capacity of carbon dioxide can still be maintained at a high adsorption capacity of 6.2 mmol / g after 10 consecutive cycle adsorption experiments. The porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent has a simple preparation process, high carbon dioxide gas adsorption capacity, and strong stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of a porous column aromatic solid amine carbon dioxide adsorbent;

[0032] Figure 2 The infrared spectra of aminopropyl silica gel and porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent;

[0033] Figure 3 is the effect of flow rate on carbon dioxide adsorption;

[0034] Figure 4 The effect of adsorbent quality on the amount of carbon dioxide adsorbed;

[0035] Figure 5 is the effect of temperature on the amount of carbon dioxide adsorption;

[0036] Figure 6 The adsorption performance was tested for 10 consecutive cycles. DETAILED DESCRIPTION

[0037] Example 1

[0038] Synthesis of brominated pillar aromatics: Under nitrogen protection and room temperature, weigh 5.5 g of 1,1-dibromophenylene diethyl ether and dissolve it in 70 ml of dry 1,2-dichloroethane solution, add 2.0 g of paraformaldehyde as a polymerization reagent, 3.5 g of boron trifluoride ether as a catalyst, stir magnetically for 1.1 hours, and pour into 120 ml of water to quench the reaction after the reaction. The solid obtained after filtration is washed with 50 ml of water and 40 ml of saturated sodium bicarbonate solution. Then dry the organic layer with 20 g of anhydrous magnesium sulfate and remove the organic solvent in vacuo. Purify the brominated pillar aromatics by column chromatography with a volume ratio of petroleum ether: ethyl acetate = 2:1.

[0039] Preparation of porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent: Weigh 3.5 grams of aminopropyl silica gel and disperse it in 140 milliliters of anhydrous toluene, add 1.4 grams of brominated columnar aromatic hydrocarbon obtained in the above steps, 1.8 grams of ethylenediamine and 0.1 grams of tetrabutylammonium bromide as catalysts, reflux at 85 degrees Celsius for 45 hours, and filter to obtain a light yellow solid powder after the reaction is completed. Wash with 80 milliliters of acetonitrile, 80 milliliters of ethanol and 60 milliliters of methanol, and then vacuum dry at 50 degrees Celsius for 20 hours to obtain ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material. Then weigh 4.0 grams of ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material and add it to 8 milliliters of collodion solution (concentration 0.025g / mL, 0.2 grams of collodion dissolved in 8 milliliters of anhydrous ethanol), stir evenly for 10 minutes, and remove the solvent under reduced pressure. The obtained material is dried and ground through a 30-mesh sieve to obtain a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The carbon dioxide adsorption process was carried out in a fixed bed reactor, and the adsorption performance was studied as follows. Figure 3-6 , the saturated adsorption capacity of carbon dioxide for 0.2g of adsorbent reached 7.8 mmol / g at 20 ml / min and 40 degrees Celsius.

[0040] Example 2

[0041] Synthesis of brominated pillar aromatics: Under nitrogen protection and room temperature, weigh 6.0 g of 1,1-dibromophenylene diethyl ether and dissolve it in 80 ml of dry 1,2-dichloroethane solution, add 2.5 g of paraformaldehyde as a polymerization reagent, 4.0 g of boron trifluoride ether as a catalyst, stir magnetically for 1.5 hours, and pour into 150 ml of water to quench the reaction after the reaction. The solid obtained after filtration is washed with 60 ml of water and 50 ml of saturated sodium bicarbonate solution. Then dry the organic layer with 25 g of anhydrous magnesium sulfate and remove the organic solvent in vacuo. Purify the brominated pillar aromatics by column chromatography with a volume ratio of petroleum ether: ethyl acetate = 3:1.

[0042] Preparation of porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent: Weigh 4.0 g of aminopropyl silica gel and disperse it in 150 ml of anhydrous toluene, add 1.6 g of brominated columnar aromatic hydrocarbon obtained in the above step, 2.0 g of ethylenediamine and 0.12 g of tetrabutylammonium bromide as catalyst, reflux at 90 degrees Celsius for 48 hours, and filter to obtain a light yellow solid powder after the reaction is completed. After washing with 100 ml of acetonitrile, 100 ml of ethanol and 80 ml of methanol, vacuum dry at 55 degrees Celsius for 24 hours to obtain ethylenediamine modified columnar aromatic hydrocarbon bonded porous silicon material. Then weigh 4.5 g of ethylenediamine modified columnar aromatic hydrocarbon bonded porous silicon material and add it to 10 ml of collodion solution (concentration 0.02 g / mL, 0.2 g of collodion dissolved in 10 ml of anhydrous ethanol), stir for 15 minutes to make it uniform, remove the solvent under reduced pressure, and the obtained material is dried and ground through a 30-mesh sieve to obtain a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The carbon dioxide adsorption process was carried out in a fixed bed reactor, and the saturated carbon dioxide adsorption capacity of 0.2g of adsorbent reached 7.7mmol / g at 20ml / min and 40 degrees Celsius.

Claims

1. A method for preparing a porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent, comprising the following steps: (1) Synthesis of brominated pillar aromatics: Dissolve 1,1-dibromophenylene diethyl ether in 1,2-dichloroethane solution, add paraformaldehyde as polymerization reagent, boron trifluoride etherate as catalyst, and react under nitrogen protection and stirring at room temperature for 1.1 to 1.5 hours. After the reaction, filter, wash, dry, and purify by column chromatography to obtain brominated pillar aromatics; (2) Preparation of porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent: aminopropyl silica gel is dispersed in anhydrous toluene, and brominated columnar aromatic hydrocarbon, ethylenediamine, and catalyst tetrabutylammonium bromide are added. The mixture is refluxed at 85-90°C for 45-48 hours. After the reaction is completed, a light yellow solid powder is obtained by filtration. The powder is washed and dried under vacuum to obtain an ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material. The ethylenediamine-modified columnar aromatic hydrocarbon bonded porous silicon material is added to an ethanol solution containing collodion, stirred evenly, and the solvent is removed under reduced pressure. The obtained material is dried, ground, and granulated to obtain a porous columnar aromatic hydrocarbon solid amine carbon dioxide adsorbent. The mass ratio of brominated columnar aromatic hydrocarbon to ethylenediamine is 0.7:1-0.9:

1.

2. The method for preparing the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent according to claim 1, characterized in that: In step (1), the mass ratio of 1,1-dibromophenylene diethyl ether to paraformaldehyde is 2.2:1 to 3.0:

1.

3. The method for preparing the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent according to claim 1, characterized in that: In step (1), the mass ratio of 1,1-dibromophenylene diethyl ether to boron trifluoride ether is 1.4:1 to 1.7:

1.

4. The method for preparing the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent according to claim 1, characterized in that: In step (2), the mass ratio of aminopropyl silica gel to brominated column aromatic hydrocarbon is 2.1:1 to 2.8:

1.

5. The method for preparing the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent according to claim 1, characterized in that: In step (2), the mass ratio of brominated pillar aromatic hydrocarbon to catalyst tetrabutylammonium bromide is 11:1 to 16:

1.

6. Use of the porous column aromatic hydrocarbon solid amine carbon dioxide adsorbent prepared by the method according to claim 1 in carbon dioxide adsorption.

Citation Information

Patent Citations

  • Preparation method and application of super-molecular carbon dioxide adsorbent used in solid and liquid states

    CN104437383A

  • Preparation and application of amino-functionalized chiral pillar[5]arene chromatographic stationary phase

    CN113181890A